2016
DOI: 10.1128/iai.00138-16
|View full text |Cite|
|
Sign up to set email alerts
|

Excreted Cytoplasmic Proteins Contribute to Pathogenicity in Staphylococcus aureus

Abstract: Excretion of cytoplasmic proteins in pro-and eukaryotes, also referred to as "nonclassical protein export," is a well-known phenomenon. However, comparatively little is known about the role of the excreted proteins in relation to pathogenicity. Here, the impact of two excreted glycolytic enzymes, aldolase (FbaA) and glyceraldehyde-3-phosphate dehydrogenase (GAPDH), on pathogenicity was investigated in Staphylococcus aureus. Both enzymes bound to certain host matrix proteins and enhanced adherence of the bacter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
42
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 52 publications
(43 citation statements)
references
References 62 publications
0
42
0
Order By: Relevance
“…Recently it has been shown that FbaA and GAPDH interact with the surface exposed major autolysin (Atl) (Ebner et al, 2016). Therefore, we considered the question whether FbaA is not excreted but bound to the cell surface from where it might be detached by PSMα and released then into the supernatant.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Recently it has been shown that FbaA and GAPDH interact with the surface exposed major autolysin (Atl) (Ebner et al, 2016). Therefore, we considered the question whether FbaA is not excreted but bound to the cell surface from where it might be detached by PSMα and released then into the supernatant.…”
Section: Resultsmentioning
confidence: 99%
“…Despite affecting viability, ECP should have an advantage in infection, which we don’t understand yet. Some of the excreted CPs such as FbaA and GAPDH may contribute to pathogenicity due to their cytotoxic activity against host cells (Ebner et al, 2016). Another possibility is that the release of CPs and RNA might overload the immune system to the benefit of the bacterium.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…These features were also observed using an insect infection model. 9 Surprisingly, when Mekonnen and collaborators correlated the virulence-gene patterns and exoprotein profiles of USA300-related isolates, they found more similarities between HA-MRSA from the Dutch and German border (HA NL-DE ; Spa t008) and HA-MRSA isolates collected in Denmark (HA DK ; Spa t024) than between these HA-MRSA and CA-MRSA from Denmark (CA DK ; Spa t008); despite the HA DK /CA DK core genome being more closely related. Interestingly, they found few differences in the expression of proteins associates with virulence including IsdA, IsdB, SCIN and Vwb.…”
mentioning
confidence: 99%